Forward thinkers will win the organizational-strategy game. Issue 10 (14th September 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings – This paper takes a fresh look at organizational strategy by considering a set of principles which, when applied in combination, will set companies apart from those who opt for earlier strategy approaches. Strategists need, for example, to be organizationally inclusive, drawing on people with the right all-round experience and knowledge as well as making the most of the small windows offered for competitive advantage. No project should outstay its welcome if it doesn't work. Practical implications – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.